Eksplorasi Perkembangan Makanan Lokal Khas Charleston: Shrimp and Grits: Exploration of the Development of Charleston's Typical Local Food: Shrimp and Grits - tanius, billy; Fatima, Queena (Universitas Pendidikan Ganesha, 2023)
Charleston, South Carolina, United States of America that is known for its history, architecture, and culinary delights. Charleston has a variety of historic local foods, one of which is Shrimp and Grits. Shrimp and Grits is a food that was introduced by a group of African settlers, Gullah Geechee in the 1600s in Southern America which was mainly consumed by the lower class people. However, the times towards culinary in the 1980s influenced the cooking style of Shrimp and Grits by chefs of Charleston which develop Shrimp and Grits and are now often consumed by various groups in the United States. This study discusses the background of Shrimp and Grits and its development in Charleston according to Charleston locals. This study uses exploratory qualitative methods in collecting data from literature studies, interviews, and observations. This research was conducted to explore the diet of Shrimp and Grits and its development in Charleston. The results of this study found that Shrimp and Grits, which were previously only known as traditional food served only in local households, are now foods that can be found in restaurants both inside and outside Charleston due to the large number of immigrant cooks who explore local food of Charleston.